Complete mitochondrial genomes of Culicoides brevitarsis and Culicoides imicola biting midge vectors of Bluetongue Virus - Khandaker Asif Ahmed; Anjana Karawita; Melissa J. Klein; Luana Fiorella Mincarelli; Barbara Secondini; Giuseppe Satta; Massimo Ancora; Cipriano Foxi; Marco Di Domenico; Michela Quaglia; Maria Goffredo; Alessio Lorusso; et al. (Mitochondrial DNA. Part B. Resources)
Biting midges (Culicoides spp.) are important vectors of several insect borne arboviruses but are underrepresented in terms of availability of high-resolution genomic resources. We assembled and annotated complete mitochondrial genomes for two Culicoides species, namely C. brevitarsis and C. imicola which are proven vectors for Bluetongue Virus (BTV). We used both long read and short read sequencing technologies to assemble the circular genomes. The genome sizes are 17,100 bp and 17,031 bp, respectively, all comprising 37 genes, including 13 protein, 22 tRNA, two rRNA coding genes, and one non-coding AT rich control region. The gene organizations and orientations are comparable to other available Culicoides mitogenomes, except for a translocation of ND2 and six tRNA genes in both C. brevitarsis and C. imicola. Eleven protein-coding genes encode a full TAA stop codon, while two (ND5, COX3) are completed by mRNA polyadenylation. Phylogenetic analysis of the mitogenomes showed C. brevitarsis and C. imicola form a monophyletic group. The sequences of these mitogenomes contribute to a baseline of molecular tools for diagnostics and surveillance for use by World Organisation for Animal Health (WOAH) reference laboratories for monitoring vectors of emerging diseases.